Waving or Drowning? Perceptions of Second Wave Feminism Through a Twenty-First Century Lens - Bralesford, Helen Margaret (2006)
This dissertation sets out to explore some twenty-first century perceptions of second wave feminism with as little mediation from the academy as possible by employing the lens of popular culture to tease out and examine some of the assumptions about the second wave that have become culturally embedded at a grass roots level.